Effect of microstructures in microchannel for single phase flow mixing intensification - Ling, Fiona W. M.; Khleif, Ali A.; Abdulbari, Hayder A. (IOP Publishing, 2020)
Enhancing flow in microchannel is a serious fundamental challenge due to the laminar flow nature of the liquids in the microscale systems that prevents the traditional viscoelastic additives from interacting with the turbulence structures (eddies) for an effective drag reduction performance. Passive drag reduction technique is believed to be a promising solution and never been investigated in the microflow systems before. In this work, micro- riblets (V-shaped) with the size ranging from 20 to 100 μm were designed, fabricated, and placed at the narrow side-walls of the rectangular microchannel in an attempt to test its flow enhancement performances. The microchannels were fabricated through a direct writing method where polymethyldisiloxane was used as the substrate. The flow behavior was investigated through monitoring the flow rate of the fluids flowing through the system. The flow profile in the system was evaluated using micro-particle velocimetry (μ-PIV). The results indicated a flow enhancement up to ~29% for a 60 μm of base-to-height riblet at an operating pressure of ~200 mbar for a single phase flow system. Larger micro-riblets were found to produce a thicker laminar sublayer within the devices that narrowed the active core of the solution.